A relação com o saber na educação a distância : a condição de ser estudante e o sentido de aprender via internet no Centro de Educação Superior a Distância da Universidade Federal de Sergipe (CESAD/UFS) - Santos, Elissandra Silva (2018)
This research aims to investigate the relationship with knowledge in Distance Education (EaD), in order to understand the condition of being a student and the meaning of learning via the internet for students at the Center for Higher Distance Education at the Federal University of Sergipe (CESAD/UFS). The importance of this research is justified by the theoreticalmethodological choice based on the Relationship with Knowledge and by the dialogue with other theoretical approaches, from which we can reflect on the meaning of learning for those who study at a distance. Thus, theoretically, this study is based on the theoretical foundations of Bernard Charlot's “Relationship with Knowledge” in the search to understand the meaning of distance learning; the ethnomethodological approach to the “Student Condition” by Alain Coulon to analyze how the condition of being a student in the distance learning modality is constituted; and Pierre Lévy in order to understand what he calls the “New Relationship with Knowledge” in the online universe. Methodologically, this is a Case Study that, under a qualitative approach, from the perspective of the Sociology of the Subject and Comprehensive, will use the “Balanços de Saber” proposed by Bernard Charlot as an instrument to identify the relationship with knowledge. The field of investigation is CESAD/UFS in its three spheres: institutional, resulting from the relationship with CESAD as UFS; the pedagogical, carried out in the Virtual Learning Environment (VLE) – the Moodle Platform; and the academic one, built in the In-Person Centers in relationships with colleagues, teachers and coordinators. The research covers all 14 (fourteen) In-Person Centers in the municipalities of Arauá, Brejo Grande, Carira, Estância, Japaratuba, Colônia 13/ Lagarto, Laranjeiras, Nossa Senhora das Dores, Nossa Senhora da Glória, Poço Verde, Porto da Folha, Propriá, São Cristóvão and São Domingos. As for the subjects, we invited students enrolled in all Distance Learning Degree Courses, namely: Biological Sciences, Physics, Geography, History, Literature-Spanish, Literature-English, Literature-Portuguese, Mathematics and Chemistry. Data collection was done through an online questionnaire via Google Forms, sent by email, subdivided into five sections to get to know the subjects in five dimensions, namely: Dimension 1: Academic profile; Dimension 2: Socioeconomic, cultural and school profile; Dimension 3: “Digital Technological Profile”; Dimension 4: Student profile in relation to the distance learning modality and the CESAD/UFS AVA; and Dimension 5: the Balance of Knowledge, in which we have testimonies about what it is like to be a distance learning and CESAD/UFS student. With the exception of Dimension 5, all other responses received statistical treatment through the Statistical Package for the Social Sciences (SPSS) with the intention of crossing variables and enabling descriptive statistics. As results, we present the types of learning expressed by the 467 (four hundred and sixty-seven) respondents to the Balanços de Saber. From their testimonies, almost all of them reflective, we were able to learn about the types of learning evoked and what they say about studying and learning remotely at CESAD/UFS. We identified additional learning – Learning Linked to Distance Study (ALED), in addition to those already validated by Bernard Charlot in his research on the relationship with knowledge: Relational and Affective Learning (ARA); Intellectual or School Learning (AIE); Learning Linked to Personal Development (ADP); Professional Learning (APro); Generic Learning (AG); Learning Linked to Everyday Life (ALVC). Finally, we affirm that we achieved the objective of knowing how the relationship with knowledge occurs at CESAD/UFS and the meaning of learning in the distance learning modality for students participating in this research